Modified shuffled frog-leaping algorithm to solve traveling salesman problem - LUO Xue-hui; YANG Ye; LI Xia (Tongxin xuebao)
Modified shuffled frog-leaping algorithm to solve TSP was proposed,which presented the concept of adjustment sequence to design the strategy of local searching,and added the mutation operation in the global exchange of information.Experimental results indicate that,compared with genetic algorithm and particle swarm optimization algorithm,the proposed algorithm has more powerful search capability and more strong robustness in solving TSP.